2021
DOI: 10.4028/www.scientific.net/ddf.406.53
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat and Mass Transfer on Steady MHD Mixed Convection Flow along a Vertical Slender Hollow Cylinder with Heat Generation and Chemical Reaction Effects

Abstract: This paper studies the effects of heat generation and chemical reaction on the coupled conjugate heat and mass transfer by MHD laminar mixed convective flow along a vertical slender hollow cylinder. The governing boundary layer equations along with the boundary conditions are first cast into a dimensionless form by a non similar transformation and the resulting equations are then solved by the finite difference method using Matlab@ following the code bvp4c. Numerical results of the velocity, temperature and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The results revealed that a rise in the magnetic field caused the boundary thermal layer to disappear, when the vortex viscosity parameter simultaneously enhanced both the heat transfer rate. Saidoune et al [15] conducted a numerical analysis to investigate the impact of chemical reactions and heat generation on the transfer of mass and heat in a laminar mixed convective flow along a thin vertical hollow cylinder, incorporating magnetohydrodynamics (MHD). Their numerical analyses within the specified parameter ranges consistently revealed that employing strong conjugate heat transfer had an adverse impact on both the Sherwood and Nusselt numbers.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that a rise in the magnetic field caused the boundary thermal layer to disappear, when the vortex viscosity parameter simultaneously enhanced both the heat transfer rate. Saidoune et al [15] conducted a numerical analysis to investigate the impact of chemical reactions and heat generation on the transfer of mass and heat in a laminar mixed convective flow along a thin vertical hollow cylinder, incorporating magnetohydrodynamics (MHD). Their numerical analyses within the specified parameter ranges consistently revealed that employing strong conjugate heat transfer had an adverse impact on both the Sherwood and Nusselt numbers.…”
Section: Introductionmentioning
confidence: 99%